Modeling of age-related neurological disease: utility of zebrafish - Kanoh, Tohgo; Mizoguchi, Takamasa; Tonoki, Ayako; Itoh, Motoyuki (Frontiers in Aging Neuroscience, 2024)
Many age-related neurological diseases still lack effective treatments, making their understanding a critical and urgent issue in the globally aging society. To overcome this challenge, an animal model that accurately mimics these diseases is essential. To date, many mouse models have been developed to induce age-related neurological diseases through genetic manipulation or drug administration. These models help in understanding disease mechanisms and finding potential therapeutic targets. However, some age-related neurological diseases cannot be fully replicated in human pathology due to the different aspects between humans and mice. Although zebrafish has recently come into focus as a promising model for studying aging, there are few genetic zebrafish models of the age-related neurological disease. This review compares the aging phenotypes of humans, mice, and zebrafish, and provides an overview of age-related neurological diseases that can be mimicked in mouse models and those that cannot. We presented the possibility that reproducing human cerebral small vessel diseases during aging might be difficult in mice, and zebrafish has potential to be another animal model of such diseases due to their similarity of aging phenotype to humans.